INVESTMENT STRATEGIES IN THE FACE OF ECONOMIC UNCERTAINTY: APPROACHES AND TOOLS FOR FINANCIAL MANAGERS (Scientific Journal of Actuarial Finance and Accounting, 2024)
Economic uncertainty has become a persistent challenge for financial managers across the globe, particularly in light of recent global crises such as the COVID-19 pandemic, geopolitical tensions, and the evolving impacts of climate change. This paper explores a variety of investment strategies that financial managers can adopt to navigate this uncertainty, focusing on both traditional approaches and modern techniques enabled by new technologies. The study discusses risk management, portfolio diversification, adaptive strategies, and the role of innovation in investment decision-making. By analyzing current literature and offering practical recommendations, this paper aims to provide valuable insights for financial professionals looking to enhance their investment strategies during periods of instability.